Increasing the risk of severe wildfires in San Dimas, Durango, Mexico caused by fire suppression in the last 60 years - Cerano-Paredes, Julián; Iniguez, Jose M.; González-Castañeda, José L.; Cervantes-Martínez, Rosalinda; Cambrón-Sandoval, Víctor H.; Esquivel-Arriaga, Gerardo; Nájera-Luna, Juan A. (Frontiers in Forests and Global Change, 2022)
To sustainably manage forests, it is important to understand the historical fire regimes including the severity, frequency, seasonal timing of fires as well as the relationship between climate and fire in order to develop management plans that mimic and/or complements the natural disturbance pattern. The objectives of this study were to reconstruct the natural fire regime within a Pinus lumholtzii site in order to understand the fire regimes within this forest type as well as adjacent more valuable mixed forests where such evidence of historical fire regimes are not available due to past timber harvesting activities. Based on 264 fire scar records we reconstruction the historical fire regimes in San Dimas, Durango, México for the last 364 years. We found a pattern of frequent fires but an absence of fire since after 1962. At this site, 98% of the fire scars were recorded during the spring season, with few fires during the summer monsoon season. The lack of fire for over six decades within these historically frequent fire forests has likely increased tree density and led to high fuel accumulations. Such conditions and combination with increasing temperatures and aridity in the region, have increased the risk of high severity wildfires that could jeopardize the sustainability of these forests and the human communities that these forests support.